A ground motion prediction equation for JMA instrumental seismic intensity for shallow crustal earthquakes in active tectonic regimes. - Campbell, Kenneth W.
The JMA (Japan Meteorological Agency) seismic intensity scale has been used in Japan as a measure of earthquake ground shaking effects since 1949. It has traditionally been assessed after an earthquake based on the judgment of JMA officials. In 1996 the scale was revised as an instrumental seismic intensity measure (IJMA) that could be used to rapidly assess the expected damage after an earthquake without having to conduct a survey. Since its revision, Japanese researchers have developed several ground motion prediction equations (GMPEs) for IJMA using Japanese ground motion data. In this paper, we develop a new empirical GMPE for IJMA based on the strong motion database and functional forms used to develop similar GMPEs for peak response parameters as part of the PEER (Pacific Earthquake Engineering Research Center) Next Generation Attenuation (NGA) project. We consider this relationship to be valid for shallow crustal earthquakes in active tectonic regimes for moment magnitudes (M) ranging from 5.0 up to 7.5?8.5 (depending on fault mechanism) and rupture distances ranging from 0 to 200 km. A comparison of this GMPE with relationships developed by Japanese researchers for crustal and shallow subduction earthquakes shows relatively good agreement among all of the relationships at M 7.0 but relatively poor agreement at small magnitudes. Our GMPE predicts the highest intensities at small magnitudes, which together with research on other ground motion parameters, indicates that it provides conservative or upwardly biased estimates of IJMA for M<5.5.
Keywords: JMA seismic intensity; Ground motion prediction equation; Regression analysis; Shallow crustal earthquakes; Active tectonic regime